Modelling of a Cantilevered Flexible Plate Undergoing Large-Amplitude Oscillations Due to a High Reynolds-Number Axial Flow - Evetts, Reilly Owen George; Howell, Richard; Lucey, Anthony (Springer, 2016)
We present a new model of the nonlinear fluid-structure interaction of a cantilevered flexible plate with an ideal flow that can account for the effect of boundary-layer separation from the plate surface upstream of its trailing edge. Short plates are studied herein for which the behaviour is dominated by low-order structural modes. When the wake is forced to form from the trailing edge the typical sequence of amplitude growth to nonlinearly saturated oscillations at flow speeds above that of the onset of linear instability is found. However, if separation is included the system evidences the same sequence at a flow speed for which the system is neutrally stable to linear disturbances. This suggests that flow separation may be the cause of the sub-critical instability found in experimental studies of the system.